Pengetahuan Stimulasi Perkembangan Anak Usia Dini oleh Guru - Panzilion Panzilion; Padila Padila; Juli Andri (Journal of Telenursing (JOTING), 2021)
This study aims to describe the knowledge of stimulation of early childhood development by the teacher. The research method used in this research is a quantitative method with a cross-sectional research design using the Chi-Square. The population in this study was 20 teachers in PAUD Aisyiyah X Gading Cempaka. The sampling technique used the total sampling technique. The results showed that the description of PAUD teacher knowledge about early childhood development stimulation in PAUD Aisyiah X Bengkulu City from 20 teachers, the excellent knowledge category was 11 respondents (50%), less than eight respondents (20%) and enough as many as two respondents (10%). In conclusion, the description of PAUD teacher’s knowledge about stimulating early childhood development in PAUD Aisyiah X Bengkulu City is mostly classified as good knowledge. Keywords: Teacher, Knowledge, Development Stimulation